Auditing: An Integrated Approach (Book). - Niles, Marcia S.; Hendrickson, Harvey S. (The Accounting Review, 1985)
Reviews the book "Auditing: An Integrated Approach," 3rd ed., by Alvin A. Arnes and James K. Loebbecke.